PRE-CONTRACTUAL OBLIGATION TO CONFIDENTIALITY OF INFORMATION IN THE PALESTINIAN CIVIL CODE DRAFT AND ITS ROLE IN MAINTAINING ECONOMIC CONTRACTUAL EQUILIBRIUM (UUM Journal of Legal Studies, 2019)
It is inconceivable that a person can be legally obliged to provide influential information to another party in order to contract freely and in an enlightened manner without requiring the latter to maintain the confidentiality of the exchanged information between the parties. In this context, Article 2.1.16 of the UNIDROIT principles of International Commercial Contracts and Article 1112-2 of the French Decree N 131-2016, etc. tend to apply the obligation to confidentiality of information at the pre-contracting phase as one of the most substantial principles governing this phase. However, the Palestinian legislature, having ignored enacting legal provisions obliging the parties to maintain the confidentiality of information in the pre-contracting phase, caused legislative deficiencies in the legislative remedies of the subject of confidentiality of information in the pre-contracting phase. A such, as a prime objective, this paper seeks to suggest orientations for the formulation of provisions for the obligation to maintain confidentiality of information in the Palestinian Civil Code Draft. Thus, an analytical comparative approach -with the French civil code- is used, while alluding briefly to German and English law, as to illustrate the Palestinian legislative deficiencies and the urgent need to legislate a legal article obligating the negotiating parties to maintain confidentiality of information, in order to contribute to the stability of civil and commercial transactions. In this regard, contractual equilibrium entails that the obligation to maintain confidentiality of information has its own independent essence from all the theories that the jurisprudence adopted as a legal basis for this obligation.